Identification of hub genes and pathways of ferroptosis in Fusarium keratitis by bioinformatics methods - Teng, Xingbo; Xiong, Xuewei; Sha, Xiaoyuan; Lei, Yahui; Diao, Yuyao; Liu, Jiayan; Tian, Yuan; Liu, Lian; Zhong, Jingxiang (Frontiers in Cellular and Infection Microbiology, 2023)
Fungal keratitis is a common blinding eye disease, and Fusarium is one of the main species that cause fungal keratitis. As is well known, oxidative stress plays an important role in Fusarium keratitis and it is also a significant initiating factor of ferroptosis. But the relationship between Fusarium keratitis and ferroptosis is currently unclear. This study aimed to speculate and validate potential ferroptosis-related genes in Fusarium keratitis using bioinformatics analysis, which provided ideas for further research on its specific mechanism and new targets for its treatment. The microarray expression profiling dataset (GSE58291) came from Gene Expression Omnibus (GEO). The differentially expressed genes (DEGs) were obtained by the limma package of the R software. It included 828 upregulated and 540 downregulated genes. The DEGs were performed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and the results found that Fusarium keratitis was related to ferroptosis. Then, the DEGs were intersected with the genes in the ferroptosis database and 26 related genes were obtained. They were mostly involved in oxidative stress, lipid peroxidation, and ferroptosis-related pathways. The top 5 hub genes were obtained by the protein-protein interaction (PPI) network analysis and the cytoHubba plug-in of Cytoscape software. They were HMOX1, CYBB, GPX2, ALOX5 and SRC. The hub genes were subjected to GSEA analysis and the enrichment results mainly included hematopoietic cell lineage, lysosome and FC gamma R mediated phagocytosis. We could see that these entries were mainly associated with iron metabolism and immune response. Then we analyzed the immune infiltration of the samples and found that T cells follicular helper, monocytes, macrophages and mast cells played an important role and correlated with hub genes. Finally, we validated the mRNA of hub genes by qPCR. HMOX1, CYBB, ALOX5 were higher expressed than the control group. GPX2 was lower expressed than the control group. SRC expression showed no statistically significant difference. So SRC might not be a hub gene. In conclusion, ferroptosis may play an important role in Fusarium keratitis.